2003
DOI: 10.1002/jmv.10336
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected distribution of hepatitis C virus genotypes in patients on hemodialysis and kidney transplant recipients

Abstract: The distribution of hepatitis C virus (HCV) genotypes in patients on hemodialysis and in kidney transplant recipients was compared with that observed in a control group composed of HCV-infected individuals from the general population. A total of 340 patients were included in the study: 46 with end-stage renal disease on regular hemodialysis treatment, 22 kidney transplant recipients and 272 controls matched for sex and age at a 4:1 ratio (controls to patient). HCV genotype was determined by sequencing of the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
(44 reference statements)
3
16
2
Order By: Relevance
“…However, the predominance of genotype 1, subtype 1a was also found in other Brazilian studies carried out among hemodialysis patients 1,8,10,15,16,19,23 . These data suggest that the high frequency of subtype 1a is probably a consequence of HCV nosocomial transmission in hemodialysis units.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, the predominance of genotype 1, subtype 1a was also found in other Brazilian studies carried out among hemodialysis patients 1,8,10,15,16,19,23 . These data suggest that the high frequency of subtype 1a is probably a consequence of HCV nosocomial transmission in hemodialysis units.…”
Section: Resultssupporting
confidence: 71%
“…Studies carried out in São Paulo 15,16,19 , Rio de Janeiro 3 , Belo Horizonte 7 , Recife 1 , Tocantins 23 , Goiás 8 and Campo Grande 10 have shown that genotype 1, subtype 1a, was prevalent in those patients. However, the genotyping methods employed in the majority of those studies (except in Goiás State), which were based on 5' NC region analyses, did not permit the correct identification of the HCV subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of HCV genotypes and subtypes found in the present study was similar to those previously reported in Brazilian hemodialysis patients (6)(7)(8)(9), who showed a predominance of HCV subtype 1a. These data suggest that subtype 1a is more likely to disseminate in the hemodialysis environment or could be more adapted to the immunosuppression of these patients (7).…”
supporting
confidence: 90%
“…These data suggest that subtype 1a is more likely to disseminate in the hemodialysis environment or could be more adapted to the immunosuppression of these patients (7).…”
mentioning
confidence: 88%
“…HCV RNA was detected by qualitative PCR using Amplicor kits (Cobas Amplicor HCV Test, Roche Diagnostic System, USA; detection limit: 50 IU/mL) and HCV genotyping was performed by sequencing the NS5B region of HCV 30 .…”
Section: Methodsmentioning
confidence: 99%